Characterization of normal adipose tissue and pansteatitic tissue in the nile crocodile (crocodylus niloticus) : possible mechanism(s) of pathogenesis and pathophysiology - Chamunrowa, Joseph Panashe (2026)
Thesis (PhD (Veterinary Anatomy and Physiology))--University of Pretoria, 2017.